Post-stratification based on a choice of a randomization device - Singh, Sarjinder; Sedory, Stephen A.; Singh, Housila P.; Arnab, Raghunath; Grewal, Inderjit Singh (Statistica, 2014)
In this paper, we use the idea of post-stratification based on the respondents’ choice of a particular randomization device in order to estimate the population proportion of a sensitive characteristic. The proposed idea gives full freedom to the respondents and is expected to result in greater cooperation from them as well as to provide some increase in the relative efficiency of the newly proposed estimator.